KAJIAN TUMBUH KEMBANG DENTOKRANIOFASIAL UNTUK KEDOKTERAN GIGI - Retno Hayati (Faculty of Dentistry, Universitas Indonesia, 2015)
The competence of dentist among other is to predict the dental and occlusion developement in the period of growth and development, and to identify dentofacial disorders in the purpose of early detection, diagnose, treatment planning and management of malocclusion and dentofacial anomaly. Therefore, it is necessary to understand the concept of growth and development, the growth pattern, the anomaly and growth development disorders, and the relevance of study dentocraniofacial growth and development in dentistry.